Extraction and its phytochemical evaluation of the crude fruit Solanum lycopersicum L - Nitin Waghamode; Patil Ravindra; Vaibhav Shilimkar; Vipul Dhasade (International Journal of Medical Toxicology and Legal Medicine, 2024)
Solanum lycopersicum, commonly known as tomato, is not only a staple in culinary practices but also a potential source of various bioactive compounds with medicinal properties. This study investigates the physicochemical attributes and phytochemical profile of S. lycopersicum, alongside its pharmacological activities, particularly focusing on antidiabetic potential. The physicochemical evaluation revealed a total ash content of 14.03%, with significant amounts of water (3.9%) and acid-insoluble ash (3.1%). Extractive values demonstrated a diverse phytochemical profile, particularly with dichloromethane extracts yielding 8.9%. The high tannin content (21%) indicates strong astringent and antioxidant properties. Preliminary phytochemical screening identified a range of compounds, including flavonoids, alkaloids, and saponins, with chromatographic analysis further supporting these findings. In pharmacological assessments, the ethanolic extract exhibited moderate alpha-amylase inhibition compared to the standard Acarbose. Furthermore, fractionation studies highlighted that specific fractions, notably E3, exhibited strong alpha-amylase inhibitory activities with an IC50 value of 65.03 µg/mL. Additionally, in vitro assays demonstrated significant alpha-glucosidase and DPP-4 inhibitory activities, indicating the potential of S. lycopersicum extracts as antidiabetic agents.